Chemosaturation with percutaneous hepatic perfusion for unresectable metastatic melanoma or sarcoma to the liver: A single institution experience. Issue 5 (19th November 2013) - Forster, Meghan R.; Rashid, Omar M.; Perez, Matthew C.; Choi, Junsung; Chaudhry, Tariq; Zager, Jonathan S.
<x xml:space="preserve">Abstract</x> Background Patients with unresectable melanoma or sarcoma hepatic metastasis have a poor prognosis with few therapeutic options. Percutaneous hepatic perfusion (PHP), isolating and perfusing the liver with chemotherapy, provides a promising minimally invasive management option. We reviewed our institutional experience with PHP. Methods We retrospectively reviewed patients with unresectable melanoma or sarcoma hepatic metastasis treated with PHP from 2008 to 2013 and evaluated therapeutic response, morbidity, hepatic progression free survival (hPFS), and overall survival (OS). Results Ten patients were treated with 27 PHPs (median 3). Diagnoses were ocular melanoma (n = 5), cutaneous melanoma (n = 3), unknown primary melanoma (n = 1), and sarcoma (n = 1). Median hPFS was 240 days, 9 of 10 patients (90%) demonstrated stable disease or partial response to treatment. At a median follow up of 11.5 months, 4 of 10 (40%) remain alive. There were no perioperative mortalities. Myelosuppresion was the most common morbidity, managed on an outpatient basis with growth factors. The median hospital stay was 3 days. Conclusions Patients with metastatic melanoma and sarcoma to the liver have limited treatment options. Our experience with PHP demonstrates promising results with minimal morbidity and should be considered (pending FDA approval) as a management option for unresectable melanoma or sarcoma hepatic metastasis. J. Surg. Oncol. 2014 109:434–439. © 2013 Wiley Periodicals, Inc.